Persepsi Aparatur Dan Penerimaan Pbb-P2 Sebelum Sesudah Penerapan Pbb-P2 Sebagai Pajak Daerah (Studi Kasus Di Kabupaten Sidoarjo) - Siswanti, Alim Nur; Junaidi, Junaidi; Harwida, Gita Arasy (AKRUAL: JURNAL AKUNTANSI, 2013)
The objective of this study was to discover of all DPPKA and UPTD officers and to examine the difference of PBB-P2 revenue as local tax with descriptive quantitative methodology. The population was 43 consisted of all DPPKAâs billing and services department, all UPTD in Sidoarjo, and all revenue PBB-P2 from 18 districts from the year of 2011 and 2012. The method of collecting data was giving questionnaire, interview, and from secondary data. The result of this study shows the difference of the PPB-P2 revenue between before and after the enactment of PBB-P2 as the local tax. This is proven that by the good perception that indicated by the officers, it is also indicated the increasing of revenue from PBB-P2, thus, the PAD of kabupaten Sidoarjo will also be increased.